Supply chain of the future: impact of the pandemic and the future prospect of food & grocery business in Singapore - Lin, Zhi Gang (Nanyang Technological University, 2022)
Covid-19 has brought the world to experience a whole new level of surprise, a whole new challenge brought down to the food and grocery industry. With the various governmental policies and restrictions being implemented on a frequent basis, food vendors who were not relevant in providing food as their core business were not allowed to operate during the early stage of the pandemic. In addition, restrictions have been placed on residents that no dine-in would be allowed in any restaurants, this causes a boom in the online food and grocery industry, as more and more users start to use online platforms to order their food and grocery. This research paper aims to identify and determine the most desired business model to aid in enhancing the operating efficiency by reducing operating cost while maintaining quality and service provided to consumers. To achieve the desired aim, interviews with various industry professionals to gain valuable insight from their years of experience and what they would expect of the future. Survey was also conducted to get an insight from the consumers perspective. Finally, this research paper would analyse the data received from all parties to aid in drafting out recommendations that would suit businesses and provide a learning point to always look out for potential strategies available.